Cohort profile: early school years follow-up of the Asking Questions about Alcohol in Pregnancy Longitudinal Study in Melbourne, Australia (AQUA at 6). Issue 1 (17th January 2022) - Muggli, Evelyne; Halliday, Jane; Elliott, Elizabeth J; Penington, Anthony; Thompson, Deanne; Spittle, Alicia Jane; Forster, Della; Lewis, Sharon; Hearps, Stephen; Anderson, Peter J
Abstract : Purpose: The Asking Questions about Alcohol in Pregnancy (AQUA) study, established in 2011, is a prebirth cohort of 1570 mother and child pairs designed to assess the effects of low to moderate prenatal alcohol exposure and sporadic binge drinking on long-term child development. Women attending general antenatal clinics in public hospitals in Melbourne, Australia, were recruited in their first trimester, followed up three times during pregnancy and at 12 and 24 months postpartum. The current follow-up of the 6–8-year-old children aims to strengthen our understanding of the relationship between these levels of prenatal alcohol exposure and neuropsychological functioning, facial dysmorphology, brain structure and function. Participants: Between June 2018 and April 2021, 802 of the 1342 eligible AQUA study families completed a parent-report questionnaire (60%). Restrictions associated with COVID-19 pandemic disrupted recruitment, but early school-age neuropsychological assessments were undertaken with 696 children (52%), and 482 (36%) craniofacial images were collected. A preplanned, exposure-representative subset of 146 children completed a brain MRI. An existing biobank was extended through collection of 427 (32%) child buccal swabs. Findings to date: Over half (59%) of mothers consumed some alcohol during pregnancy, with one in five reporting at least one binge-drinking episode prior to pregnancy recognition. Children's craniofacial shape was examined at 12 months of age, and low to moderate prenatal alcohol exposure was associated with subtle midface changes. At 2 years of age, formal developmental assessments showed no evidence that cognitive, language or motor outcome was associated with any of exposure level. Future plans: We will investigate the relationship between prenatal alcohol exposure and specific aspects of neurodevelopment at 6–8 years, including craniofacial shape, brain structure and function. The contribution of genetics and epigenetics to individual variation in outcomes will be examined in conjunction with national and international collaborations.